2019 Practice guidelines for thyroid core needle biopsy: a report of the Clinical Practice Guidelines Development Committee of the Korean Thyroid Association - Jung, Chan Kwon (J Pathol Transl Med, 2020)
Ultrasound-guided core needle biopsy (CNB) has been increasingly used for the pre-operative diagnosis of thyroid nodules. Since the Korean Society of the Thyroid Radiology published the ‘Consensus Statement and Recommendations for Thyroid CNB’ in 2017 and the Korean Endocrine Pathology Thyroid CNB Study Group published ‘Pathology Reporting of Thyroid Core Needle Biopsy’ in 2015, advances have occurred rapidly not only in the management guidelines for thyroid nodules but also in the diagnostic terminology and classification schemes. The Clinical Practice Guidelines Development Committee of the Korean Thyroid Association (KTA) reviewed publications on thyroid CNB from 1995 to September 2019 and updated the recommendations and statements for the diagnosis and management of thyroid nodules using CNB. Recommendations for the resolution of clinical controversies regarding the use of CNB were based on expert opinion. These practical guidelines include recommendations and statements regarding indications for CNB, patient preparation, CNB technique, biopsy-related complications, biopsy specimen preparation and processing, and pathology interpretation and reporting of thyroid CNB.